2022
DOI: 10.18844/ijlt.v14i4.7064
|View full text |Cite
|
Sign up to set email alerts
|

The ‘Hidden’ curriculum in higher education in Ghana: The perception of language students in the college of education

Abstract: A holistic curriculum or education seeks to develop all three domains of learning: cognitive, psychomotor and affective. While the cognitive domain focuses on the mental and psychological fortitude of learners, the psychomotor focuses on the use and development of muscular or motor skills and the affective domain deals with the feelings, emotions and attitudes of students. Interestingly, not all these domains are sufficiently written or documented as guidelines or curricula for classroom practice. It is for su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…While teachers' educational lives are equipped with their own knowledge and learning, they have many beliefs, attitudes and values related to education and learning (Uzunboylu & Altay, 2021;Tılıç, 2020;Ünsal, 2019). The difficult situations that an individual may encounter in a short time are stereotyped in the pattern of self-efficacy and how high the education level will be in the future (Cervone, Mercurio, & Lilley, 2020;Fenyi & Sapaty, 2022). In learning, the teacher is the facilitator and mediator, so the teacher is assigned to design learning that can optimise students' knowledge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While teachers' educational lives are equipped with their own knowledge and learning, they have many beliefs, attitudes and values related to education and learning (Uzunboylu & Altay, 2021;Tılıç, 2020;Ünsal, 2019). The difficult situations that an individual may encounter in a short time are stereotyped in the pattern of self-efficacy and how high the education level will be in the future (Cervone, Mercurio, & Lilley, 2020;Fenyi & Sapaty, 2022). In learning, the teacher is the facilitator and mediator, so the teacher is assigned to design learning that can optimise students' knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…In a study, it was concluded that teachers, in particular, create awareness that is beyond what they teach in the classroom, and 'how' they teach also unconsciously teaches lessons. This situation leads to the conclusion that teachers, especially primary school teachers, are responsible for their education and behaviour in the classroom (Fenyi & Sapaty, 2022). Menon, Leng, Naimie, Danaee, and Abuzaid (2021) tried to examine the measurable steps of teachers and how this affects students' learning.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the audiovisual tool, which is among the healthy skills, will allow the application of all visual sounds in its formulation and will ensure the learning of healthy skills and innate knowledge. To develop a working process that will contribute to language formation in learning, listening and speaking (Anatolievna & Vladislavovna, 2015;Fenyi & Sapaty, 2022;Putra & Dwirandra, 2019).…”
Section: Introductionmentioning
confidence: 99%